(untitled) (Perner’s Contacts, 2017)
Parallel paths (concurrency) of connections in the public passenger transport has a negative impact on the distribution of subsidies for different types of public passenger transport. In coordination of connections the railway passenger transport and bus services should be assessed several aspects, such as the profitability of operation, time availability, spatial accessibility and continuity of connections, also need to take into account the extent of the transport infrastructure in the specific area.